Learning curve for the transsphenoidal endoscopic endonasal approach to pituitary tumors. (1st November 2016) - Qureshi, Talha; Chaus, Fahad; Fogg, Louis; Dasgupta, Mona; Straus, David; Byrne, Richard W.
Abstract: Introduction: The transsphenoidal endoscopic approach is a relatively new procedure compared to the microscopic approach in pituitary adenoma resection. The endoscopic approach has shown to significantly decrease the rate of complications, time in the operating room and hospital, and patient post-op discomfort. However, this procedure requires the surgeon to make use of different visual and tactile clues that must be developed with experience. Therefore, it is important to understand the learning curve that the surgeon must overcome to become proficient with the endoscopic approach. Methods: Retrospective review of a single-surgeon consecutive series of 78 patients undergoing endoscopic pituitary tumor surgery from 2006 to 2012 at Rush University Medical Center has been used in this study. Patients were grouped according to an early ( n = 9) and late group ( n = 68) determined by a significant difference in outcomes. Our primary outcome measures were: duration of operation, CSF leak, hospital length of stay, visual field improvement, diabetes insipidus, panhypopituitarism, and subtotal resection. Results: There was a significant reduction in OR time and intraoperative CSF leaks between the early and late groups. There was no difference in hospital LOS or visual field improvement between the groups. With regards to complication rates, there was no difference found for DI, panhypopituitarism, lumbar drain placement, sinusitis, or subtotal resection between the two groups. Conclusion: This study indicates that there may be a learning curve of approximately 9 cases before a surgical team can decrease OR times and reduce the rate of intraoperative CSF leaks for the endonasal endoscopic approach to pituitary adenoma resection.